The Weakening of The Role of Islamic Religious Counselors in Forming Sakinah Families in Padangsidimpuan Batunadua District - Roni, Muhammad Arman Syahroni; Misrah, Misrah (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2024)
Household disharmony, often stemming from limited understanding of marital rights and responsibilities, continues to challenge the formation of sakinah families in Padangsidimpuan Batunadua District. This issue persists despite the presence of Islamic Religious Counselors whose central role is to guide couples in achieving marital tranquility aligned with Islamic teachings. This study aims to examine how Islamic Religious Counselors contribute to shaping sakinah families and to identify the factors that support or hinder their efforts. A qualitative method was employed, with data gathered through observations, interviews, and documentation. Data analysis followed Miles and Huberman’s procedures. The results indicate that Islamic Religious Counselors exert a substantial influence by providing religious guidance, pre and post marital counseling, and community based educational program aimed to reinforcing moral principles and mutual understanding. Nevertheless, the effectiveness of these efforts is constrained by inadequate facilities and a shortage of certified counselors, compelling reliance on basic religious study forums to address family issues. Enhancing infrastructural support and expanding counselor certification programs may therefore improve the quality and reach of religious counseling services, ultimately fostering more harmonious and resilient family units.